Concurrent cetuximab and postoperative radiation in resected high‐risk squamous cell carcinomas of the head and neck: A single‐institution experience. Issue 9 (7th April 2016) - Araki, Daisuke; Redman, Mary W.; Martins, Renato; Eaton, Keith; Baik, Christina; Chow, Laura; Goulart, Bernardo; Lee, Sylvia; Santana–Davila, Rafael; Liao, Jay; Parvathaneni, Upendra; Laramore, George; et al.
Abstract: Background: Postoperative cisplatin and radiation is the standard of care for high‐risk squamous cell carcinoma of the head and neck (SCCHN). We have used cetuximab and radiation in the postoperative setting for patients deemed poor candidates for cisplatin. Methods: We retrospectively identified 40 patients who received cetuximab and radiation for resected locoregionally advanced SCCHN between 2006 and 2013 at our institution. Results: The 2‐year Kaplan–Meier estimates were: overall survival (OS) 41%, recurrence‐free survival (RFS) 34%, locoregional control 63%, and distant metastatic control 59%. Eastern Cooperative Oncology Group (ECOG) performance status ≥1 predicted for inferior OS (hazard ratio [HR] = 5.43; p = .003), RFS (HR = 4.07; p = .007), and locoregional control (HR = 4.92; p = .04) in multivariate analysis. Conclusion: Patients with resected high‐risk SCCHN treated with postoperative cetuximab and radiation have suboptimal therapeutic outcomes. Further study of the efficacy and cost‐effectiveness compared to radiation alone is warranted. © 2016 Wiley Periodicals, Inc. Head Neck 38: 1318–1323, 2016